Epidemiology of age-related macular degeneration among the elderly population in Thailand - Rossukon Khotcharrat (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To estimate the prevalence and associated factors of age-related macular degeneration (AMD) in Thailand. Material and Method: This cross-sectional survey was undertaken in 2010. Five provinces were selected and people aged 50 years and over were invited for eye examination. Demographic and health behaviors and data from eye examination equipment were registered. Ophthalmologists graded AMD as early or late based on fundus color photograph and image from optical coherence tomography. Logistic regressions were analyzed to establish association factors for AMD. Results: Of the 7,043 participants, AMD was found in 862 people (12.2%), with more than half (53.1%) found in both eyes. Most cases (94.3%) were early dry, 1.8% early wet, 3.4% late dry, and 0.7% late wet AMD. Factors positively associated with AMD were age (OR 1.03, 95% CI 1.02-1.04), diabetes mellitus (OR 1.20, 95% CI 1.03-1.39), and consumption of yellow vegetable (OR 2.32, 95% CI 1.23-4.39). Factors that conversely associated with AMD were consumption of green vegetable (OR 0.51, 95% CI 0.33-0.79), physical exercise (OR 0.67, 95% CI 0.51-0.87), high blood pressure (OR 0.75, 95% CI 0.63-0.89), and heavy drinking habit (OR 0.45, 95% CI 0.26-0.75). Conclusion: The prevalence of AMD in Thai population age 50 and over was 12.2%. More than half (53.1%) of the cases were found in both eyes, but few at severe stages. The present study confirmed age and DM as positive associated factors, and green vegetable, exercise as negative associated factors. Further research should investigate the effects of hypertension, yellow vegetable, and alcohol drinking on AMD.